Comparison of CuBr-laser frequency operation modes; Proceedings of SPIE; Vol. 9810 : Atomic and Molecular Pulsed Lasers XII - Fedorov V. F. Valery Fedorovich (Gas and Plasma Lasers, Metal Vapor, 2015)
Title screen